2007
DOI: 10.1142/s0218194007003276
|View full text |Cite
|
Sign up to set email alerts
|

Automating Functional Testing of Components From Uml Specifications

Abstract: A method of functional testing for software components according to model-based testing techniques is proposed. Test cases are generated from UML diagrams and OCL constraints that comprise a component interface and realization specification. The method uses a reduced set of UML artifacts that constitute the main requirements for its application along with a component development process, making use of development artifacts. Also, the set of generated test artifacts are packed together with the provided compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…Only five articles were found that could be assigned to the analysis phase [47,81,104,117,143]. Gerlich et al [81] propose an approach that automatically generates test cases based on information about the source code (prototype specification and code structure).…”
Section: Category Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…Only five articles were found that could be assigned to the analysis phase [47,81,104,117,143]. Gerlich et al [81] propose an approach that automatically generates test cases based on information about the source code (prototype specification and code structure).…”
Section: Category Automationmentioning
confidence: 99%
“…Furthermore, this approach includes automated test evaluation and comprehensive presentation of results. The method described in [47] allows performing conformance evaluation considering different levels. Xie et al [104] present an approach that focuses on analyzing and maintaining test scripts in order to be more efficient.…”
Section: Category Automationmentioning
confidence: 99%
“…LTSs são amplamente utilizados como formalismo semântico de muitas notac ¸ões de especificac ¸ão [Jard and Jéron 2005] e, por isso, podem ser facilmente obtidos de especificac ¸ões funcionais usando ferramentas de conversão, como por exemplo UMLAUT [Ho et al 1999]. Além disso, LTSs também são amplamente utilizados como o modelo do qual os casos de teste podem ser obtidos, por exemplo, nas ferramentas SPACES [Barbosa et al 2007], TGV [Jard and Jéron 2005], LTS-BT [Cartaxo et al 2008] e TaR-GeT [Nogueira et al 2007]. LTS é um grafo dirigido -dígrafo -no qual vértices são chamados de estados e arestas de transic ¸ões.…”
Section: Sistema De Transic ¸õEs Rotuladasunclassified
“…Besides, the automation can reduces the cost of the testing process since it reduces the time of test cases creation [17]. Other advantage of using MBT is the possibility of reusing development artifacts, particularly requirements documents [4].…”
Section: Model-based Testingmentioning
confidence: 99%